4.5 kV Bi-mode Gate Commutated Thyristor design with High Power Technology and shallow diode-anode - Lophitis, Neophytos; Antoniou, Marina; Udrea, Florin; Vemulapati, Umamaheswara; Arnold, Martin; Rahimo, Munaf; Vobecky, Jan (My University, 2016)
The Bi-mode Gate Commutated Thyristor (BGCT) is a reverse conducting Gate Commutated Thyristor (GCT) where the diode regions are intertwined with GCT parts. In this work we examine the impact of shallow diode-anodes on the operation of the GCT and propose the introduction of optimised High Power Technology (HPT+) in the GCT part. In order to assess and compare the new designs with the conventional, a multi-cell mixed mode model for large area device modelling was used. The analysis of the simulation results show that the shallow diode does not affect the MCC whereas the introduction of the HPT+ allows for a step improvement.
Keywords: Anodes; Diodes; Electrodes; Integrated circuits; Reconfigurable hardware; Semiconductor diodes; Thyristors